Implementing Robust Data Privacy and Security in Modern ERP Systems: A Technical Deep Dive - Sathyananda Kumar Pamarthy (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Enterprise Resource Planning (ERP) systems have become crucial components in modern business operations, demanding robust security measures to protect sensitive data and maintain operational integrity. This comprehensive article explores the multifaceted aspects of ERP security, focusing on advanced access control mechanisms, data protection strategies, and compliance requirements. The implementation of Role-Based Access Control (RBAC), multi-factor authentication, and biometric verification has significantly enhanced security protocols while improving operational efficiency. Data protection measures, including end-to-end encryption and dynamic data masking, have strengthened the defense against cyber threats across various industry sectors. The evolution of regulatory compliance has necessitated substantial investments in security infrastructure, leading to enhanced audit capabilities and improved risk management. Customer confidence and business partner integration have been reinforced through transparent security practices and secure collaboration frameworks. Looking ahead, emerging technologies such as artificial intelligence, blockchain, and zero-trust architecture are reshaping ERP security landscapes, promising more robust protection against evolving cyber threats while maintaining operational efficiency and user convenience.